The Influence of Job Analysis, Workload Analysis, And Motivation On Employee Performance at The Investment and One-Stop Integrated Services Office of Simalungun Regency - Butar - Butar, Lindu Verawati; Sipayung, Tuahman; Purba, Tioner (Jurnal Ilmiah Accusi, 2025)
This study aims to analyze the influence of job analysis, workload analysis, and motivation on employee performance at the Investment and One-Stop Integrated Services Office. A quantitative approach was used with a survey method, involving 52 respondents who are employees at the agency. Data analysis was conducted using multiple linear regression with the help of SPSS software. The results of the study indicate that simultaneously, the three independent variables have a positive and significant effect on employee performance. Partially, job analysis has a positive and significant effect on employee performance. Similarly, workload analysis also has a positive and significant effect on employee performance. In addition, motivation has a positive and significant effect on employee performance. Based on these results, it can be concluded that improving the quality of job analysis, proper workload planning, and strengthening work motivation are effective strategies for enhancing employee performance in the government environment of Simalungun Regency